Indirectness and politeness in request strategies of Javanese male Indonesian EFL learners - Dewi Cahyaningrum; Djatmika; Joko Nurkamto (Universitas Syiah Kuala, 2026)
This study examined how Javanese male EFL learners employed indirectness and politeness strategies when making requests in formal contexts. It drew on the frameworks of Searle (1975), Trosborg (1994), and Brown and Levinson (1987) to explore how learners manage face-threatening acts (FTAs) using pragmalinguistic devices. The analysis focused on head acts (core requests) and external modifications. Using a qualitative case study design, four male university students from Central Java, Indonesia, were involved as participants. Data were collected through role-play tasks and interviews and analyzed using Miles and Huberman’s (2014) model. The findings showed that the learners preferred conventionally indirect strategies (56.25%), often employing politeness markers and expressions of ability to mitigate the FTAs and respect the hearer’s autonomy. Direct strategies (43.75%) were less common and primarily occurred in urgent situations but were mitigated with politeness markers. External modifications, particularly supportive reasons, appeared in 81.25% of cases, highlighting a strong orientation towards respecting the hearer’s autonomy, or ‘negative face’. This pattern reflects sensitivity to formal contexts, supporting Brown and Levinson’s claim that politeness strategies support smoother interactions in such settings. These results challenge the stereotype that male speakers tend to be more direct. Instead, the participants prioritized indirectness and external modifications, influenced by contextual factors and cultural values such as 'andhap asor' (humility) and 'tepa selira' (empathy), which promote social harmony and minimize confrontation. This study highlights the roles of culture, gender, and context in shaping politeness strategies.